2018
DOI: 10.1371/journal.pone.0200752
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin1 regulates Th1 and Th17 effector responses but is not required for experimental autoimmune encephalomyelitis

Abstract: Multiple Sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system (CNS) where pathology is thought to be regulated by autoreactive T cells of the Th1 and Th17 phenotype. In this study we sought to understand the functions of Presenilin 1 (PSEN1) in regulating T cell effector responses in the experimental autoimmune encephalomyelitis (EAE) murine model of MS. PSEN1 is the catalytic subunit of γ-secretase a multimolecular protease that mediates intramembranous proteolysis. γ-secretas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Interestingly, both CD4 + and CD8 + T cells expressed PSEN1 , a gamma secretase component known to cleave Notch receptors ( NOTCH1/2/3 ) 122 that were expressed by both T cell linages in plaque. This signaling is involved in T cell function and may contribute to the observed T cell activation 123 , differentiation 124 , PD-1 expression and regulation of cytolytic functions 125 in our plaques. Our analysis also revealed that T cells expressing the same ligands could interact through distinct receptor pairs on CD4 + and CD8 + T cells in SYM and ASYM plaques.…”
Section: Resultsmentioning
confidence: 74%
“…Interestingly, both CD4 + and CD8 + T cells expressed PSEN1 , a gamma secretase component known to cleave Notch receptors ( NOTCH1/2/3 ) 122 that were expressed by both T cell linages in plaque. This signaling is involved in T cell function and may contribute to the observed T cell activation 123 , differentiation 124 , PD-1 expression and regulation of cytolytic functions 125 in our plaques. Our analysis also revealed that T cells expressing the same ligands could interact through distinct receptor pairs on CD4 + and CD8 + T cells in SYM and ASYM plaques.…”
Section: Resultsmentioning
confidence: 74%
“…It is known that cholesterol metabolism is affected via modulation of the enzymes involved in sterol biosynthesis, such as sterol-C5-desaturase (SC5D), 24-dehydrocholesterol reductase (DHCR24), squalene monooxygenase (SQLE), and lecithin-cholesterol acyltransferase (LCAT). Dysregulation of sterol biosynthesis is strongly implied in neurodegenerative pathology like AD . Other molecules concerned with AD and MS pathologies are also affected in astroglia on EBV infection such as those involved in lipid transport pathway (involving ABCA-1, APOE, and APOA1) and microtubule cytoskeleton proteins (PLP-1, MAP-2, and APP), , in addition to PMP-22 (peripheral myelin protein-22) and other membrane proteins (matrix metalo-endopeptidases or MME, BACE-1, and sonic hedgehog or SHH). Some other molecules including glutamate ionotropic receptor NMDA type subunit 1 (GRIN1) and sodium voltage-gated channel α subunit 11 (SCN11A) were also reported in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…Bai et al found that stem cells played a therapeutic role mainly through a paracrine secretion-related immune regulation, rather than self-regeneration (Bai et al, 2012). Th1 lymphocytes, which are known as CD4+IFN-γ+ T cells and characterized by the secretion of IFN-γ, have been proven to be closely linked to the pathogenesis of EAE (Cummings et al, 2018). Li et al found that MSCs could promote the recovery of neural function in EAE mice by increasing the proportion and function of CD5+IL-10 + B cells (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%